A program quality framework: a collaborative teaching team approach to quality assurance, quality enhancement and staff capacity building - van de Mortel, Thea; Mitchell, Creina; Shuker, Mary-Ann; Needham, Judith; Kain, Victoria; Sanger, Georgina; Pierce, Beth (Frontiers in Medicine, 2023)
A global shortage of registered nurses provides a further impetus to retain nursing students and graduate safe nurses. While various frameworks support curriculum design and describe the need for ongoing curriculum evaluation and monitoring, there is little in the literature to support the enactment and ongoing quality enhancement of curricula. Translation of the curriculum plan into the delivered curriculum relies on academics who may or may not be adequately prepared for course writing and teaching in higher education settings, despite their discipline expertise. Additionally, there are well recognised issues of curriculum drift where curriculum innovations and changes are whittled away over time by incremental changes to courses that interfere with the integrity of the accredited curriculum. We propose an evidence-based Program Quality (ProQual) Framework that takes a holistic, collaborative, and systematic approach to monitoring and enhancing curriculum quality and program delivery over the life of the curriculum while developing staff capability and scholarship.